Assessment of Pontianak City Elementary School Students' Motor Skills - Sabransyah, Mohammad (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2025)
Objective. This study employs a quantitative approach with a descriptive design, focusing solely on providing descriptions. Materials and Methods. The participants in this study comprised all upper grade students from Elementary School 20 in Pontianak City, totaling 37 students, which included 20 males and 17 females. The entire population was utilized as the sample for this study. Results. The comprehensive findings of the study indicated that there was 1 student (2.70%) in the very good category, 9 students (24.32%) in the good category, 15 students (40.54%) in the moderate category, 10 students (27.03%) in the less category, and 2 students (5.41%) in the very less category. The most prevalent occurrence was found in the moderate category, accounting for 40.54%. Conclusion. The findings of the study indicated that the gross motor skills of upper grade students at State Elementary School 20 in Pontianak City fell within the moderate category. The findings of the study indicated that the gross motor skills of senior students at Elementary School 20 in Pontianak City fell within the moderate range. Consequently, it is advisable for educators and educational institutions to enhance physical activities that can foster the growth of students' gross motor skills, including traditional games, organized sports, and outdoor pursuits. Moreover, it is advisable to conduct additional investigations to examine the elements that affect gross motor skills and to identify more effective intervention strategies.